THE NEW PUBLIC SERVICE PARADIGM COMMUTER LINE KRL SERVICES ENFORCEMENT PERIOD OF RESTRICTIONS ON EMERGENCY ACTIVITIES - Fadli Bas Bastian (GEMA PUBLICA, 2022)
This research discusses aboutimplementation of public services during the Pandemic on Commuterline KRL based on the rules for the implementation of Emergency Community Activity Restrictions (PPKM) to level extensions based on the humanist paradigm.In serving passengers, there are problems that make it difficult for customers using Commuter Line KRL transportation services to get Commuter Line KRL transportation services, such asBased on the Circular Letter of the Minister of Transportation number 50 of 2021 concerning Amendments to the Circular Letter of the Minister of Transportation number 42 of 2021.Regarding the rules for the Worker Registration Certificate (STRP) it is stated in the Circular Letter (SE) of the Minister of Transportation Number 50 of 2021. In the Circular it is stated that during the Emergency PPKM on the Commuter Line KRL it only serves critical and essential sector workers in the agglomeration area, as evidenced by the possession of a Letter of Intent. Worker Registration Certificate (STRP) or similar certificate. Passengers who do not bring the letter will not be allowed to ride the KRL Commuter Line. The purpose of this research is to investigate how far the humanist paradigm of commuter line KRL services in DKI Jakarta during the Pandemic is through the Humanist Paradigm. The NPS seeks to persuade people to fulfill their responsibilities as citizens. The method used in this research is descriptive method, qualitative approach. With the number of informants as many as 10 (ten) people who were determined by using purposive sampling technique 3 people and accidental sampling 7 people. Data collection techniques used are observation, interviews and documentation. In addition, test the validity of the data using the Triangulation method. New public service (NPS) which places more emphasis on organizational humanism. A model of public service that recognizes that they interact with the government not only as customers but as citizens. The quality of public services today and the challenges in the future are expected to be able to contribute a little in improving the quality of public services.Keywords: Public Service, Commuter line KRL, Humanist Paradigm, Quality, Emergency PPKM